The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1964
DOI: 10.1126/science.144.3622.1122
|View full text |Cite
|
Sign up to set email alerts
|

Homocitrulline and Homoarginine Synthesis from Lysine

Abstract: After the injection of L-lysine and uniformly labeled L-lysine-carbon-14 into the rat, labeled homocitrulline and homoarginine are found in the liver and kidney. The ingestion of lysine by seven normal adults results in an increased urinary excretion of homocitrulline and homoarginine. These data suggest the occurrence of an unreported metabolic pathway for lysine in the rat and man.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
37
1
1

Year Published

1967
1967
2014
2014

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 78 publications
(41 citation statements)
references
References 8 publications
2
37
1
1
Order By: Relevance
“…This may be due to the fact that the kidney is one of the sites for the transaminidation of L-lysine to homoarginine. 21,22 In the LURIC study, homoarginine consistently was found to be low in patients with a low estimated glomerular filtration rate, 23 and hemodialysis patients (4D study) had even lower concentrations. Because homoarginine is synthesized from the amino acid lysine and is suggested to indicate intestinal absorption of exogenous amino acids, 24 it is likely that homoarginine plays a role in the nutritional status of patients.…”
Section: Discussionmentioning
confidence: 99%
“…This may be due to the fact that the kidney is one of the sites for the transaminidation of L-lysine to homoarginine. 21,22 In the LURIC study, homoarginine consistently was found to be low in patients with a low estimated glomerular filtration rate, 23 and hemodialysis patients (4D study) had even lower concentrations. Because homoarginine is synthesized from the amino acid lysine and is suggested to indicate intestinal absorption of exogenous amino acids, 24 it is likely that homoarginine plays a role in the nutritional status of patients.…”
Section: Discussionmentioning
confidence: 99%
“…Elevated plasma a-aminoadipic acid and homoarginine, two metabolites of L-Lys, in group Lys indicated that the rats in group Lys had increased intestinal absorption of L-Lys. [23][24][25] However, the elevation of plasma Lys in group Lys was not statistically significant. As far as we examined, plasma Ala, Pro, Arg, Gln, Asn, homoarginine, and a-aminoadipic acid in group Lys seemed to play some roles in the suppression of vascular calcification.…”
Section: L-ly Protected the Femora From Osteoporotic Changes In Adenimentioning
confidence: 83%
“…Homoarginine is a naturally occurring amino acid derived from lysine, produced mainly in the kidney 31 and found at low concentrations in most bodily fluids. 32,33 Low plasma homoarginine has been associated with decreased renal function, energy metabolism, and NO regulation.…”
Section: Discussionmentioning
confidence: 99%
“…In vivo 31 P magnetic resonance spectroscopy measurements were performed as described previously. 28 At 7-T field strength with the use of a quadrature 31 P coil, spectra were selected from voxels of 160 to 230 µL in the cerebrum of AGAT wild-type (WT; n=5), AGAT −/− (n=4), and AGAT −/− Cr (n=1) mice.…”
Section: Magnetic Resonance Spectroscopy Measurementmentioning
confidence: 99%
See 1 more Smart Citation